2020
DOI: 10.21203/rs.3.rs-29830/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human papillomavirus infection and cervical intraepithelial neoplasia progression are associated with increased vaginal microbiome diversity in a Chinese cohort

Abstract: Background: In this study, the association between human papillomavirus (HPV) infection and related cervical intraepithelial neoplasia (CIN) or cervical cancer and vaginal microbiome was evaluated in Chinese cohorts. Methods: The vaginal bacterial composition of five groups, HPV-infected women without CINs (HPV, n=78), women with low-grade squamous intraepithelial lesions (LSIL, n=51), women with high-grade squamous intraepithelial lesions (HSIL, n=23), women with invasive cervical cancer (Cancer, n=9) and hea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…Hydrogen peroxide and bacteriocins produced by Lactobacillus hindering the proliferation of other microorganisms too [6]. Even in the CA group of our study, Lactobacillus was still the most abundant genus, although less than 50% [18]. Therefore, a large number of Lactobacillus existing might lead to the small variety of bacteria.…”
Section: Discussionmentioning
confidence: 59%
“…Hydrogen peroxide and bacteriocins produced by Lactobacillus hindering the proliferation of other microorganisms too [6]. Even in the CA group of our study, Lactobacillus was still the most abundant genus, although less than 50% [18]. Therefore, a large number of Lactobacillus existing might lead to the small variety of bacteria.…”
Section: Discussionmentioning
confidence: 59%
“…CST-IV doubled in women who had low-grade squamous intraepithelial neoplasia (LSIL), increased threefold in women with high-grade squamous intraepithelial neoplasia (HSIL), and fourfold in women with invasive disease. Women with HSIL exhibited higher abundance of Peptostreptococcus anaerobius and Anaerococcus tetradius, and depletion in L. crispatus as opposed to women with LSIL [70,72].…”
Section: Preinvasive and Invasive Cervical Cancer And The Vaginal Microbiomementioning
confidence: 91%
“…External carcinogenic factors like contraceptive use and cigarette smoking that are found to be causes of cancer have also been associated with BV. Dysbiosis of the vaginal microbiome with a depleted Lactobacillus population can support HPV infection [72,73]. Additionally, an acute inflammation caused by BV may play a role in cervical cancer by the influence of the antimicrobial proteins and immune cell populations in the vagina [74].…”
Section: Preinvasive and Invasive Cervical Cancer And The Vaginal Microbiomementioning
confidence: 99%
“…The promotion of in ammation and remodeling of the ECM results in mutagenesis that may promote the onset and progression of cancer [53]. Studies have shown that Anaerococcus is involved in progression of cervical intraepithelial neoplasia [54,55] and bladder cancer [56]. Therefore, the increase of Anaerococcus may be related to progression of breast cancer.…”
Section: Discussionmentioning
confidence: 99%